Identification of Secondary Metabolite Compounds in Nut Grass (Cyperus rotundus L.) Using Different Solvents Types - Arief Rahman; Rusli Anwar; Yuliana Sabarina Lewar (Universitas Muhammadiyah Sorong, 2023)
Nutgrass is a common weed often found in agricultural fields. Its high population in agricultural land can have negative implications for farmers as it may prevent farmed crops from growing and producing as well. However, nutgrass has the potential to be developed into a biopesticide due to its phytochemical compounds. The purpose of this study is to identify secondary metabolite compounds present in nutgrass extract. On nutgrass extracts, the study used phytochemical screening techniques with ethanol (polar) and n-hexane (non-polar) solvents. According to the findings, ethanol and n-hexane solvents produced nutgrass extract yields of 10.81% and 0.65%, respectively. Alkaloids, flavonoids, saponins, tannins, and steroids were all present in nutgrass extracts made with ethanol, whereas only steroid components were present in extracts made with n-hexane. Saponins, tannins, alkaloids, flavonoids, and steroids are only a few of the secondary metabolite substances found in nutgrass extracts.